Gonadotrophins versus clomifene citrate with or without intrauterine insemination in women with normogonadotropic anovulation and clomifene failure (M-OVIN): a randomised, two-by-two factorial trial. Issue 10122 (24th February 2018) - Weiss, Nienke S; Nahuis, Marleen J; Bordewijk, Esmee; Oosterhuis, Jurjen E; Smeenk, Jesper MJ; Hoek, Annemieke; Broekmans, Frank JM; Fleischer, Kathrin; de Bruin, Jan Peter; Kaaijk, Eugenie M; Laven, Joop SE; Hendriks, Dave J; et al.
Summary: Background: In many countries, clomifene citrate is the treatment of first choice in women with normogonadotropic anovulation (ie, absent or irregular ovulation). If these women ovulate but do not conceive after several cycles with clomifene citrate, medication is usually switched to gonadotrophins, with or without intrauterine insemination. We aimed to assess whether switching to gonadotrophins is more effective than continuing clomifene citrate, and whether intrauterine insemination is more effective than intercourse. Methods: In this two-by-two factorial multicentre randomised clinical trial, we recruited women aged 18 years and older with normogonadotropic anovulation not pregnant after six ovulatory cycles of clomifene citrate (maximum of 150 mg daily for 5 days) from 48 Dutch hospitals. Women were randomly assigned using a central password-protected internet-based randomisation programme to receive six cycles with gonadotrophins plus intrauterine insemination, six cycles with gonadotrophins plus intercourse, six cycles with clomifene citrate plus intrauterine insemination, or six cycles with clomifene citrate plus intercourse. Clomifene citrate dosages varied from 50 to 150 mg daily orally and gonadotrophin starting dose was 50 or 75 IU daily subcutaneously. The primary outcome was conception leading to livebirth within 8 months after randomisation defined as any baby born alive after a gestational age beyond 24 weeks. Primary analysis was by intention to treat. We made two comparisons, one in which gonadotrophins were compared with clomifene citrate and one in which intrauterine insemination was compared with intercourse. This completed study is registered with the Netherlands Trial Register, number NTR1449. Findings: Between Dec 8, 2008, and Dec 16, 2015, we randomly assigned 666 women to gonadotrophins and intrauterine insemination (n=166), gonadotrophins and intercourse (n=165), clomifene citrate and intrauterine insemination (n=163), or clomifene citrate and intercourse (n=172). Women allocated to gonadotrophins had more livebirths than those allocated to clomifene citrate (167 [52%] of 327 women vs 138 [41%] of 334 women, relative risk [RR] 1·24 [95% CI 1·05–1·46]; p=0·0124). Addition of intrauterine insemination did not increase livebirths compared with intercourse (161 [49%] vs 144 [43%], RR 1·14 [95% CI 0·97–1·35]; p=0·1152). Multiple pregnancy rates for the two comparisons were low and not different. There were three adverse events: one child with congenital abnormalities and one stillbirth in two women treated with clomifene citrate, and one immature delivery due to cervical insufficiency in a woman treated with gonadotrophins. Interpretation: In women with normogonadotropic anovulation and clomifene citrate failure, a switch of treatment to gonadotrophins increased the chance of livebirth over treatment with clomifene citrate; there was no evidence that addition of intrauterine insemination does so. Funding: The Netherlands Organization for Health Research and Development.